Artificial nighttime lighting impacts Plasmodium falciparum mature stage V gametocytes infectivity in Anopheles stephensi - Jose Luis Llergo; Helena Garuti; Celia Lopez; Julia Sanchez; David Calvo (Malaria Journal, 2024)
Abstract Background Malaria is one of the most important vector-borne diseases of humans with an estimated 241 million cases worldwide in 2020. As an urban and periurban mosquito species, Anopheles stephensi is exposed to artificial human stimuli like light that can alter many aspects of mosquito behaviour, physiology and metabolism. Therefore, fluctuations in the light environment may influence the host, parasite and/or mosquito biology and hence modulate risk for disease transmission. In this study, the effect of artifitial light at night on mosquito infectivity by Plasmodium falciparum during the first hours of blood digestion was tested. Methods A total of three independent standard membrane feeding assays were performed to artificially fed septic and aseptic mosquitoes with P. falciparum infected blood. After blood feeding, females were transferred to incubators with different photoperiod cycles, so digestion occurred under day artificial light or dark. At 7 and 16 days post blood feeding, mosquitoes were dissected for midguts and salivary glands, respectively. Percentage of mosquitoes fed, percentage of prevalence and P. falciparum oocyst intensity between septic and aseptic mosquitoes in the two different photoperiod regimes, were compared using a Kruskal-Wallis test followed by a Dunn´s multiple comparison test . Results The exposition of mosquitoes to light after they took an infected blood meal has a negative effect on the successful progression of P. falciparum in the mosquito midgut. Antibiotic treatment significantly incremented the number of oocysts per midgut. Photophase significantly reduced the median oocyst intensity in both septic and aseptic mosquitoes. The percentage of oocyst reduction, understood as the percentage of reduction in the mean oocyst intensity of the parasite in the mosquito midgut between photophase and scotophase, was 51% in the case of aseptic mosquitoes and 80% for septic mosquitoes, both in the photophase condition. Conclusion Although there are still many gaps in the ...